Optimasi Pembebanan Pada Sistem Penerangan DC Pembangkit Listrik Tenaga Akumulator Gandeng Sebagai Sumber Energi Cadangan - Cekmas Cekdin (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
– frequent power outages from PLN will have an impact on activities in household or offices for lighting. The utilization of accumulators is worth considering, because the use of accumulators as an energy source has not been utilized optimally, especially for the fulfillment of energy needs on site and for certain uses, such as utilization in isolated locations. In order for the DC lighting system of the accumulator power plant that is arranged parallel as a backup energy source to work continuously or for a long time, it must be loaded with optimal load. Research is done by increasing the load gradually, which is useful to find out at what load so that there is a critical voltage in one of the accumulators. Research was also conducted without using additional photovoltaic chargers or using additional photovoltaic chargers. From the results of research when the DC lighting system of the accumulator power plant is arranged parallel as a backup energy source without using an additional photovoltaic charger at a maximum load of 160 Watts there is a critical voltage in one of the accumulators. And when the DC lighting system of the Accumulator Power Plant is paralleled as a backup energy source using an additional photovoltaic charger at a maximum load of 160 Watts or more, there is no critical voltage of 11.5 Volts in one of the accumulators, meaning that the DC lighting system of the Accumulator Power Plant which is parallel stacked as a backup energy source works continuously. Keywords : Accumulator, maximum load, critical voltage, optimal.